Impact of precursor-derived peracetic acid on post-weaning diarrhea, intestinal microbiota, and predicted microbial functional genes in weaned pigs - Galgano, Salvatore; Conway, Leah; Fellows, Adrian; Houdijk, Jos (Frontiers in Microbiology, 2024)
Post-weaning diarrhoea affects piglets in the nursery phase of the production, leading to a substantial impact both at farm and financial level. The multifactorial etiology of this disease includes housing conditions, pig genetics, microbial composition and metagenomic assets. Amongst the common therapeutic approaches, the widely used zinc oxide underwent a European Union ban in 2022 due to its negative environmental impact and correlation to increased antimicrobial resistance. During this study, we have tested two levels of inclusion of the potential antimicrobial alternative peracetic acid, delivered in water via the hydrolysis of the precursors sodium percarbonate and tetraacetylethylenediamine, in comparison to zinc oxide and an untreated control during a two-week animal study. We assessed the microbial composition, predicted metagenome, together with performance and physiological parameters in order to describe the microbial functional role in etiopathology.Both zinc oxide and peracetic acid resulted in the amelioration of the diarrhetic status by the end of the trial period, with noticeable zinc oxide effects visible from the first week. This was accompanied by an improved performance when compared to the first week figures, and a decreased stomach pH in both peracetic acid levels. A significant reduction in both stomach and caecal Proteobacteria was recorded in the zinc oxide group and a significant reduction of Campylobacter in the stomach was reported for both zinc oxide and one of the peracetic acid concentrations. Amongst other functional differences, we found that the predicted ortholog for the zonula occludens toxin, a virulence factor present in pathogens like Escherichia coli and C. jejuni was less abundant in the stomach of treated pigs compared to the control group. In water peracetic acid delivered via precursor hydrolysis has the potential to be a valid intervention, alternative to antimicrobial, to assist weaning of piglets. Our findings support the view that postweaning diarrhoea is a complex multifactorial disease with an important metagenomic component characterized by the differential abundance of specific predicted orthologs and microbial genera in the stomach, and caecum of pigs.